Media-Related Out-of-School Contact with English in Germany and Switzerland Frequency, Forms and the Effect on Language Learning - Krüger, Maleika (Springer Nature, 2023)
This open access book aimes to close a critical research gap in understanding how frequently German-speaking adolescents come into contact with the English language through various media channels, such as television, books, or the internet, and how this contact influences learners' English competences. In addition, this research project explores the effect of family background and gender on this contact. The analysis shows frequent contact with English-language media content by young learners in Germany and Switzerland. More frequent contact was associated with higher language competences. Differences could be found in the preferences of media content and type of media channels due to socio-economic family background and gender.